The Protection of Whistle-blowers within the Latest Initiatives of the Council of Europe - Badźmirowska-Masłowska, Katarzyna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The protection of whistle-blowers under the Article 10 of ECHR has faced a lot of com-plex problems, which had been a result from the implications of ICT`s development and change of the media environment. The COE is involved in a worldwide debate about changes taking places in a contemporary legal system in the context of the protection of human rights. Therefore, the review of the latest legal initiatives (resolutions, recommendations, etc.) as well as other activities in the field concerned might be helpful to put the question-able issues.As the article is of the introductory character, further analysis is required. Within the human rights approach, it should concern, in particular the legal status of the whistle-blower and the issues, pertaining to legal and alternative ways of her/his protection.